2020
DOI: 10.1111/asj.13449
|View full text |Cite
|
Sign up to set email alerts
|

Fat depot‐specific effects of body fat distribution and adipocyte size on intramuscular fat accumulation in Wagyu cattle

Abstract: In beef cattle, the accumulation of intramuscular adipose tissue within longissimus muscle, called marbling, is important for determining the quality grade of beef. Japanese black cattle (Wagyu) are characterized by the ability to accumulate high amounts of intramus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Studies have shown that fat deposition in backfat is related to body fat percentage, carcass cross-sectional fat area ratio, intramuscular fat, and flavor and juiciness of beef ( 5 , 6 ). In Japanese Wagyu cattle, IMF content in the longest dorsal muscle was found to be positively correlated with the percentage of subcutaneous fat and maturity in vivo ( 7 , 8 ). Therefore, the identification of key genes related to subcutaneous adipose tissue by a new method is an important strategy for carcass and meat quality genetic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that fat deposition in backfat is related to body fat percentage, carcass cross-sectional fat area ratio, intramuscular fat, and flavor and juiciness of beef ( 5 , 6 ). In Japanese Wagyu cattle, IMF content in the longest dorsal muscle was found to be positively correlated with the percentage of subcutaneous fat and maturity in vivo ( 7 , 8 ). Therefore, the identification of key genes related to subcutaneous adipose tissue by a new method is an important strategy for carcass and meat quality genetic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…IMF can be used to store energy and functions during exercise, but an excessive accumulation of IMF in the muscle is related to many diseases in people, such as diabetes, insulin resistance, lipodystrophy, etc. ( Goodpaster et al, 2000 ; Shoelson et al, 2007 ; Tada et al, 2020 ; Yamada et al, 2020 ). The IMF content in animals is not only an important index of high quality of meat but also an important character of good germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1 , the longissimus muscle (LM) of Wagyu cattle contains the highest IMF content (31.8-37.8% from two publications of Irie et al. (2011) and Yamada et al. (2020) .…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Numerous studies agreed that there is a positive correlation between the quantity of intramuscular adipocytes and the increased adipogenesis in fetal muscle ( Yamada et al., 2020 , Chen et al., 2019 , Park et al., 2018a ). Calves will form fewer intramuscular preadipocytes if they experience undernutrition conditions in late fetal and neonatal stages.…”
Section: Nutritional Factorsmentioning
confidence: 99%